Sporadic parathyroid adenoma: an updated review of molecular genetics - Chorti, Angeliki; Cheva, Angeliki; Chatzikyriakidou, Anthoula; Achilla, Charoula; Boulogeorgou, Kassiani; Despoina, Krokou; Milias, Stefanos; Zarampoukas, Thomas; Papavramidis, Theodossis (Frontiers in Endocrinology, 2023)
Introduction: Primary HPT (PHPT) is a common disorder, affecting approximately 1% of the general population. Parathyroid adenomas emerge as non-familial sporadic in 90% of cases. The aim of this review is to give a detailed update of molecular genetics of sporadic parathyroid adenoma reported in international literature. Methods: A bibliographic research was conducted in Pubmed, Google Scholar and Scopus. Results: Seventy-eight articles were included in our review. CaSR , MEN1, CCND1/PRAD, CDKI, angiogenic factors like VEGF, FGF, TGFβ and IGF1 and apoptotic factors are important genes in parathyroid adenomas pathogenesis that have been established by several studies. A huge list of proteins are differently expressed in parathyroid adenomas measured by Western Blotting, MALDI/TOF, MS spectrometry and immunohistochemistry. These proteins take part in several cell processes such as cell metabolism, cytoskeleton structural stability, cell oxidative stress regulation, cell death, transcription, translation, cell connection and cell signaling transmission, while the can be found over- or underexpressed in abnormal tissues. Conclusion: This review gives a detailed analysis of all reported data on genomics and proteomics of parathyroid adenoma. Further studies should be applied on understanding parathyroid adenoma pathogenesis and introducing new biomarkers for early detection of primary hyperparathyroidism.